Evidence-Based Guidelines for Labor Support that Promote Vaginal Birth. Issue 2 (March 2023) - Bernstein, Samantha L.
Abstract : The Association of Women' Health, Obstetric and Neonatal Nurses has published evidence-based clinical practice guidelines Labor support for intended vaginal birth to support nurses who care for patients during labor and birth. Our maternity nursing expert, Dr. Bernstein, summarizes the guidelines.